Husband Support Affects Self Efficacy in Pregnant Women During the Covid 19 Pandemic - Nanik Handayani; Fritria Dwi Anggraini (Jurnal Ilmiah Kesehatan, 2021)
The period of the Covid 19 pandemic is a difficult time for all people, including pregnant women. In undergoing pregnancy, pregnant women must have self-efficacy, and husband support is needed. This paper determines the correlation between husband support and self-efficacy in pregnant women. This study was an analytical research design with a cross-sectional approach. The population was 52 pregnant women checked at Independent Midwifery Practice (IMP) Nanik Cholid, Sidoarjo, from May to November 2020. Meanwhile, the sample size was 46 respondents by purposive sampling. The independent variable was husband support, and the dependent variable was self-efficacy in pregnant women. The instrument to evaluate husband support was Family Support Questionnaire (FSQ), and to assess self-efficacy was a questionnaire with a Likert scale. Then, data were analyzed with the Spearmen Rank test with a significance (α) of 0.05. The results showed that most respondents had good self-efficacy (91.3%) and received high husband support (65.2%), particularly emotional support (28%). The statistical tests result using the Rank Spearmen test obtained p=0.016 indicating a correlation between husband support and self-efficacy in pregnant women. In conclusion, Husband support increases self-efficacy in pregnant women during the COVID 19 Pandemic. Health workers should educate husbands to provide support to pregnant women during pregnancy.